Danny Chung Sums It Up - Chan, Maisie; Quek, Natelle (New York, NY : Amulet Books, 2023)
When his Chinese grandmother comes to live with his family in England, an eleven-year-old aspiring comic book artist has to share his bedroom with Nai Nai, who does not speak English, but they soon share a bond through math and art.
"Originally published in the United Kingdom in 2021 by Piccadilly Press, under the title Danny Chung does not do maths"--Hardcover edition.
new kids book 2025 spring.
School Library Journal, August 2021
Publishers Weekly, September 2021
Kirkus Review, July 2021
4.8.
Keywords: Grandmothers -- Fiction; Family life -- England -- Fiction; Art -- Fiction; Mathematics -- Fiction; Chinese -- Fiction